Impact Of Scheduling Drugs Under The 1971 Convention On Psychotropic Substances The Benzodiazepines Reappraised*. - Navaratnam, V.

(untitled)
Concern over the abuse of psychoactive substances, particularly amphetamines and barbiturates, emerged early in the 50's. In an attempt to bring about unified action for the control of these psychoactive substances a special international control instrument - the 1971 Convention on Psychotropic Substances - was introduced. The major aims of the Psychotropic Convention are to control the production, marketing (sale on prescription only), exportation and importation of psychotropic substances which have dependence producing liability.